Elucidating the anatomy of a rare communicating bronchopulmonary foregut malformation (CBPFM) in a preschool child. Issue 1 (11th January 2021) - Shama, Niveditha; Mathai, John; Rai, Ekta; Kodiatte, Thomas Alex
Abstract : Communicating bronchopulmonary foregut malformations (CBPFMs) are complex and rare anomalies. Their characteristic feature is an anomalous communication between the respiratory system (trachea, lung or bronchus) on one side and the gastrointestinal tract (oesophagus or stomach) on the other. Though acquired CBPFMs are known, the large majority of them are congenital and single. CBPFMs often go undetected even at surgery and require more than one operation before they are successfully addressed. This is because the symptomatology of CBPFM resembles the more common oesophageal atresia (OA) with tracheoesophageal fistula, wherein it may coexist. We report a patient with OA who had a rare form of CBPFM where the upper lobe of the right lung communicated with the upper oesophagus. This account highlights a novel method of working out the uncertain anatomy, in such cases. There may be associated anomalies of the lung parenchyma and vasculature usually involving the pulmonary arterial supply to the affected lung. Clinical, radiological, endoscopic and pathological characterisation permit precise diagnosis in most instances, with an occasional case that defies definition.